Jenis dan Populasi Musuh Alami Hama Padi pada Sistem Tanam Jajar Legowo - Sholahuddin, Sholahuddin; Huwaida, Salma Nabila; Wijayanti, Retno; Supriyadi, Supriyadi; Subagya, Subagya; Sulistyo, Ato (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2023)
Natural enemies play an important role in the rice field ecosystem in achieving pest population balance. The jajar legowo planting system is a planting system that provides empty space for rows of plants that are thought to affect the types and population dynamics of natural enemies. The aim of this study was to determine the effect of applying the jajar legowo cropping system to the types and populations of natural enemies of rice pests. The research was conducted from April-June 2022 in Karanglo Village, Polanharjo, Klaten and the Laboratory of Plant Pests and Diseases, Faculty of Agriculture, Universitas Sebelas Maret. The research was carried out in rice fields with conventional spacing systems (tegel) and jajar legowo 2:1. The variables observed were the type and population of predators and parasitoids along with the degree of parasitization of the rice pests. The results showed that the types of predators found in conventional land and Jajar Legowo were not different. The application of the jajar legowo cropping system increased the population of Paederus and Tetragnatha spider.